Ammonia-acetylene PECVD coating on wound dressing to control delivery of silver sulfadiazine - Somruthai Tunma (2018)
© 2018, Walailak University. All rights reserved. A novel wound dressing surface modification was developed by applying plasma-enhanced chemical vapor deposition (PECVD). The cotton wound gauze dressings were treated by the mixed composition of 10 %NH3+He and 10 %NH3+C2H2plasmas followed by immersion in silver sulfadiazine (AgSD) solution. A high functionality and a high surface area can thus be obtained by plasma deposition of C2H2+ NH3. We reported the effect of a strong interaction between AgSD and cotton gauze yarn by observing the reactive amorphous carbon layer. It had an ability to slow down the release rate of AgSD compounds into the solution, reported as the UV-visible absorbance of the solution released from the plasma-treated gauze. The results showed that the release rate of AgSD molecules was lower, compared to the untreated gauze. Scanning electron microscopy (SEM) micrographs showed the interaction between AgSD and the cotton fibers of the plasma-treated gauze. In the untreated gauze, no such interaction was found. According to the energy dispersive X-ray spectroscopy (EDS) data, %weight of the Ag compound on the treated gauze was higher than the untreated gauze. A test on the antibacterial effect, using Fluid Thioglycollate Medium (FTM) as the culture media, clearly demonstrated that the plasma treated gauze which was immersed with AgSD, had ability to inhibit bacterial growth.